Working with archive material. A revision of social assistants professional training documents between 1930 and 1932 in Federal Capital (Papeles, 2025)
This article emerges as a part of a wider inquiry process about the scientific, ideological and political discourses that were present in the first Social Service’s professional training centres in Argentina, particularly in the experience of the Social Service School of the Social Argentine Museum in 1930. As an expression of a complex and diverse process, we propose this route through different documents since revising -at the same time- the experience that occurred in Santiago de Chile, with the first School founded in 1925.Since a materialist perspective of discourse analysis, we revise fundaments, profiles, ways of institutional organization, training proposals in respect of social assistance, aspects that were treated on different articles published in the Argentine Social Museum´s Newsletter about the Social Service School’s project and finally its creation. Since this publication’s relevance – which consisted in a newsletter -  as to give a public debate space about Estate politics, and the presence on this debate of people with different trajectories and renowned in the politics space, we consider that it is key to recover these discussions to place in tension the professional’s social function in its origins.
Keywords: social assistants; social visitors; functions; professional training; professional profile